A novel cut-off grade method for increasing the sustainability of underground metalliferous mining operations. (1st October 2021) - Sotoudeh, Farzad; Nehring, Micah; Kizil, Mehmet; Knights, Peter; Mousavi, Amin
Highlights: A review of technical concepts in integration of underground pre-concentration systems. Introducing a novel method for underground cut-off grade determination. Increasing the sustainability of underground mines. Investigation of a bulk ore sorter in a sublevel stoping mine, followed by potential benefits. Abstract: The determination of a cut-off grade is considered to be one of the main steps in the design and strategic planning of mining operations. This is due to its role in distinguishing between waste material and valuable ore. This becomes increasingly important as the mining industry is facing lower grades within an uncertain market. The implementation of pre-concentration systems prior to main processing has significant potential to increase the sustainability and resource utilisation of mining operations, which can result in the reduction of mine cut-off grade. This paper reviews the technical concepts of integration of pre-concentration systems into underground mines and presents a novel method for underground cut-off grade calculation. The proposed model is implemented on a sublevel stoping operation to illustrate the impacts and advantages of the underground pre-concentration integration. The outputs of this study and investigation of various scenarios prove an increase in the profitability, efficiency and sustainability of the underground operations.